2007
DOI: 10.1007/s00436-007-0620-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Experimental Cystoisospora canis Infection Models in Beagle Puppies and Efficacy Evaluation of 5 % Ponazuril (Toltrazuril sulfone) Oral Suspension

Abstract: In a pilot study, three pairs of Beagle puppies were inoculated with 2.5, 3.75 or 5 x 10 4 sporulated oocysts of Cystoisospora canis. All exhibited patent infections within ten days post-inoculation. In an efficacy study, 33 puppies were given 5 x 10 4 oocysts of C. canis and randomly allocated to receive 20, 30, 40, or 50 mg/kg ponazuril on day 0, or 30 mg/kg ponazuril or placebo on days 0 and 7. Clinical health observations and oocyst excretion were monitored daily post treatment. All dosages decreased oocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Buehl et al (2006) reported that 2 3 10 4 oocysts of C. canis obtained from dogs in Austria were pathogenic for 3-wk-old beagle puppies. Results of the present study support those of Buehl et al (2006), Mitchell et al (2007), and Reinemeyer et al (2007) and confirm that C. canis is a primary pathogen in young dogs.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Buehl et al (2006) reported that 2 3 10 4 oocysts of C. canis obtained from dogs in Austria were pathogenic for 3-wk-old beagle puppies. Results of the present study support those of Buehl et al (2006), Mitchell et al (2007), and Reinemeyer et al (2007) and confirm that C. canis is a primary pathogen in young dogs.…”
supporting
confidence: 82%
“…Oral inoculation of 5 3 10 4 oocysts of our isolate of C. canis used in the present study from Brazil caused similar clinical signs and prepatent and patent periods in 6-wk-old recipients, as did inoculation of 5 3 10 4 oocysts of an isolate of C. canis obtained from dogs from Virginia Reinemeyer et al, 2007) in 6-wk-old pups. An isolate of C. canis from Illinois was not pathogenic for 6-wk-old pups inoculated with 1 3 10 5 sporulated oocysts (Lepp and Todd, 1974).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…To the authors' knowledge there is no published data regarding treatment of S. neurona in cats; ponazuril therapy was initiated given its effectiveness against S. neurona in horses (5–10 mg/kg for 28 days) 31 and its use in dogs and cats for the treatment of other protozoal infections 16,32–34 . The recommended anticoccidial dose in cats is 7.5–15 mg/kg 16 and doses >30 mg/kg and up to 50 mg/kg have been demonstrated to have better efficacy and equal safety margins in a group of research Beagles 34 . Based on these findings, a loading dose of 50 mg/kg was administered for 4 days and the lower dose was administered at discharge.…”
Section: Discussionmentioning
confidence: 99%